1994
DOI: 10.1002/aja.1001990206
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splice form of type II procollagen mRNA (IIA) is predominant in skeletal precursors and non‐cartilaginous tissues during early mouse development

Abstract: Type I1 collagen, generally considered to be characteristic of cartilage, has been localized in specific non-cartilaginous structures during embryogenesis and development of the skeleton. Type I1 procollagen is synthesized in two different forms generated by alternative splicing of exon 2 in the precursor mRNA transcript. One form (type IIA procollagen) contains a large cysteine-rich domain in the NH,-terminal propeptide, while the second form (type IIB procollagen) does not. These two forms are spatially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 182 publications
(172 citation statements)
references
References 23 publications
(22 reference statements)
8
159
1
2
Order By: Relevance
“…The expression in the myocardium remains until E13.5 when Zac1 is also expressed in the valve tissue, but is remarkably downregulated at E15.5. It is noteworthy that the expression of Zac1 in the heart is concordant with the localization of the type II collagen splice variant IIA, which is found during early myocardial differentiation when dual-layered ventricular myocardium develops to form trabeculations (Cheah et al, 1991;Ng et al, 1993;Sandell et al, 1994). Zac1, like collagen type IIA, is not expressed when myocardium forms a multi- Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The expression in the myocardium remains until E13.5 when Zac1 is also expressed in the valve tissue, but is remarkably downregulated at E15.5. It is noteworthy that the expression of Zac1 in the heart is concordant with the localization of the type II collagen splice variant IIA, which is found during early myocardial differentiation when dual-layered ventricular myocardium develops to form trabeculations (Cheah et al, 1991;Ng et al, 1993;Sandell et al, 1994). Zac1, like collagen type IIA, is not expressed when myocardium forms a multi- Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The a1 type XI oligonucleotide hybridized to a band of approximately 6.5 kb and the control a1 type I oligonucleotide probe hybridized with two RNA bands of approximately 5.3 and 7.1 kb. As a control for specificity of the type I, IIA, and IIB collagens, probes were hybridized to tissues where the distribution could be predicted by previous results from our laboratory (Sandell et al, 1991(Sandell et al, , 1994 and others (Nah and Upholt, 1991) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Procollagen IIA contains the second exon of the procollagen I1 gene and is only expressed in chondroprogenitor cells (Sandell et al, 1991(Sandell et al, , 1994. The comparison showed that in all locations the expression of the chondroprogenitor cell specific procollagen IIA and M-twist were mutually exclusive.…”
Section: -Dmentioning
confidence: 99%